The Reconstruction of Lower Extremity Mohs Surgical Wounds With Keystone Fasciocutaneous Flaps: Outcomes From 259 Consecutive Cases. Issue 5 (May 2021) - Thorpe, Ryan B.; Cook, Jonathan L.
Abstract : Supplemental Digital Content is Available in the Text.